MODELING AND OPTIMIZATION ON ENERGY CONSUMPTION OF A HYBRID POWER INSTALLATION FOR A VEHICLE - А. Y. Afanasiev; N. A. Rybushkin; K. A. Kilimanov (Известия высших учебных заведений: Проблемы энергетики)
The object of research is a hybrid power installation of a bus with a diesel engine and a synchronous electric motor. The purpose of the work is the development of engineering models of a synchronous electric motor and a diesel engine, the search for optimal electric currents control laws for electric motor and optimal bus moving laws with a hybrid power installation for general energy consumption. Synchronous electric drive and internal combustion engine models were used, convenient for research, analytical and numerical methods of parametric optimization and optimal control were used. Parameter values and laws of vehicle motion with energy saving are obtained.